MEMAHAMI PRAKTEK BAGI-HASIL KEB MASYARAKAT KAMPAR RIAU (Sebuah Pendekatan Etnografi) - Iwan Triyuwono, Eko Ganis Sukoharsono (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This study is aimed to grasp the meaning of a rubber revenue-sharingfrom the point of view of people who understand the revenue-sharing practice inKampar community through participatory observation. Additionally, it is aimed to deepen the understanding of revenue-sharing practice in Kampar Riau community. This study uses a qualitative method with Etnography approach. Data were collected through participation observation and open in-depth interviews. The data were analyzed using Spradley model (1997), with includes domainanalysis, taxonomic analysis, componential analysis and cultural analysis. Theresults of this study were that gotah revenue-sharing is revenue-sharingcontaining the value of KESOJUKAN (Keadilan/Justice, Kesosialan/Socialism,Kejujuran/Honesty and Keamanahan/Trustworthiness) in which Gotah revenue-sharing is a traditional custom practiced by generation and based on Islamic values.